Survival outcomes analysis according to mismatch repair status in locally advanced rectal cancer patients treated with neoadjuvant chemoradiotherapy - Chen, Lin; Yang, Xudong; Zhang, Yuanyuan; Liu, Jie; Jiang, Qixin; Ji, Fang; Gao, Jinli; Zhou, Zhuqing; Wang, Hao; Huang, Jun; Fu, Chuangang (Frontiers in Oncology, 2022)
Background The predictive role of mismatch repair (MMR) status for survival outcomes and sensitivity in neoadjuvant chemoradiotherapy settings for patients with locally advanced rectal cancer (LARC) has been inconclusive. Methods A retrospective cohort of patients with LARC treated with neoadjuvant chemoradiotherapy (nCRT) was recruited. After adjusting for baseline characteristics, we used propensity score matching to reduce the effect of potential confounding factors on MMR status. The primary analysis was based on overall survival as the more important endpoint. Results This study included 269 patients. Patients with defective MMR (dMMR) were younger (58.5% vs. 60.0%, p=0.0274) and had lower body mass indices (p=0.0091), higher differentiation grades (p=0.0889), and more advanced rectal cancers (clinical T4 or T4b, p=0.0851; M1, p=0.0055) than those with proficient MMR (pMMR). However, propensity score-matched patients with dMMR (p=0.0013) exhibited superior overall survival, even in the M1 subgroup. More importantly, patients with proficient MMR who undergo early pathological downstaging, especially lymph node pathological downstaging, can achieve a prognosis similar to that of patients with dMMR. Conclusion The clinical significance of this retrospective study mainly includes two points: (1) Data from our study confirmed that LARC patients with dMMR status had better overall survival rates after nCRT, even in the M1 subgroup. (2) Similar survival outcomes were observed in older and female patients with early lymph node pathological downstaging, regardless of dMMR or pMMR.